Survival and healthcare utilization of infants diagnosed with lethal congenital malformations. (December 2018) - Nguyen, Jacqueline; Salemi, Jason; Tanner, Jean; Kirby, Russell; Sutsko, Ronald; Ashmeade, Terri; Salihu, Hamisu; Drach, Laura
Abstract Objective: We assessed survival, hospital length of stay (LOS), and costs of medical care for infants with lethal congenital malformations, and also examined the relationship between medical and surgical therapies and survival. Study design: Retrospective cohort study including infants born 1998–2009 with lethal congenital malformations, identified using a longitudinally linked maternal/infant database. Results: The cohort included 786 infants: trisomy 18 (T18, n = 350), trisomy 13 (T13, n = 206), anencephaly (n = 125), bilateral renal agenesis (n = 53), thanatophoric dysplasia/achondrogenesis/lethal osteogenesis imperfecta (n = 38), and infants > 1 of the birth defects (n = 14). Compared to infants without birth defects, infants with T18, T13, bilateral renal agenesis, and skeletal dysplasias had longer survival rates, higher inpatient medical costs, and longer LOS. Conclusion: Care practices and survival have changed over time for infants with T18, T13, bilateral renal agenesis, and skeletal dysplasias. This information will be useful for clinicians in counseling families and in shaping goals of care prenatally and postnatally.